Enhancing the detection of natural thermal entanglement with disorder. - Hide, J; Son, W; Vedral, V (2009)
Physical systems have some degree of disorder present in them. We discuss how to treat natural, thermal entanglement in any random macroscopic system from which a thermodynamic witness bounded by a constant can be found. We propose that functional many-body perturbation theory be applied to allow either a quenched or an annealed average over the disorder to be taken. We find, when considering the example of an XX Heisenberg spin chain with a random coupling strength, that the region of natural entanglement detected by both witnesses can be enhanced by the disorder.